Teenagers And Instagram: The Impact Of Becoming Instagram High Users Among High School Students In Surakarta - Likha Sari Anggreni; Gaza Daffa Redfada; Monika Sri Yuliarti; Muhammad Yunus Anis (Jurnal Ilmu Komunikasi, 2019)
The development of technology has a tremendous impact on human life,including teenagers. Since Instagram has become an increasingly social mediadevelopment, adolescents in the city of Surakarta are also no less behind. This studytries to explore the impact of becoming Instagram high users among high schoolstudents in Surakarta, especially those related to the motivation of activities carriedout by celebrities on their Instagram accounts. The respondents involved in thisstudy were 10th grade students from SMA Negeri 1 and SMA Negeri 3 Surakarta,using simple random sampling technique. Meanwhile, the data collection techniquewas carried out by using an online questionnaire, using a Google form which wasfilled intensively accompanied. The findings of this study are, in general therespondents are active Instagram users who can be included in the heavy userscategory. However, activities imitating the behavior of celebrities who are mostlynegative are not carried out in daily life. Further research that can be done is toexamine the specifics and depth, what factors influence the imitation of celebritybehavior through Instagram.